4x-3+6x+8=90

Simple and best practice solution for 4x-3+6x+8=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-3+6x+8=90 equation:


Simplifying
4x + -3 + 6x + 8 = 90

Reorder the terms:
-3 + 8 + 4x + 6x = 90

Combine like terms: -3 + 8 = 5
5 + 4x + 6x = 90

Combine like terms: 4x + 6x = 10x
5 + 10x = 90

Solving
5 + 10x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 10x = 90 + -5

Combine like terms: 5 + -5 = 0
0 + 10x = 90 + -5
10x = 90 + -5

Combine like terms: 90 + -5 = 85
10x = 85

Divide each side by '10'.
x = 8.5

Simplifying
x = 8.5

See similar equations:

| 2m^2+4m^2+m+2=0 | | 2m^2+1+4m^2+m+2=0 | | 2m^21+4m^2+m+2=0 | | x=y+5.00 | | 9x^2+61x-14=0 | | x^2-18x=3 | | -0.166666666x=7 | | 9y-6+x+8=42 | | 3(m+2)= | | 9n^2+30+25=0 | | 6a^2+41a-56=0 | | m^4+5m-36=0 | | 2/5+(1/3-1/5)= | | 9x^2-60x+100=0 | | 7n^2+34n-48=0 | | 12x+6=90 | | -.5u+.6=.1666666667 | | 7x-8+4x-3=8x+7 | | -t^2+6t-5=0 | | 16-(-2x-4)-(5x-3x+4)=-(-x+7)-(6x-4-7) | | t^2+6t-5=0 | | -4(1-8p)=252 | | -15x^2+90+10-85=0 | | 2/4*4=6 | | [24-6x]=38 | | 4+x=5x-44 | | 5x+10=14+3x | | 6.00x-20.00=20.00 | | -1/4+5= | | 7x+7=27+5x | | 16x+19=4x+1 | | 6.00x-20.00=10 |

Equations solver categories